Adoption of Production Practices of Paddy by Tribal Farmers - M.A. Kareem; P.L. Manohari (Journal of Agricultural Extension Management, 2025)
Large number of technologies have been evolved in the field of agriculture but are not being accepted and adopted at its fullest extent by the farmers. The gap between recommendations by the scientists and actual use by farmers is still existing. Supe et .al (1983) and Jaiswal (1985) reported a substantial technological gap in respect of use of seed rate, fertilisers and plant protection measures by farmers. Number of factors may be responsible for the existing adoption gap. The speedy adoption of improved agricultural technologies and innovations are most important for enhancing agricultural production at faster rate and hence it is a crucial aspect under innovation diffusion process.